Imagining a positive future reduces cortisol response to awakening and reactivity to acute stress. (June 2020) - Nicolson, Nancy A.; Peters, Madelon L.; in den Bosch - Meevissen, Yvo M.C.
Highlights: Daily visualization of a best possible self improved mood and reduced worrying. This 2-week intervention lowered cortisol response to a social stress task. The cortisol response to awakening also decreased after the intervention. Cortisol changes may reflect less worrying, greater positive affect. Abstract: The positive influence of optimism on health is thought to be due in part to a reduced physiological response to stress, as manifested for instance in activity of hypothalamic-pituitary-adrenal (HPA) systems. Results of previous studies support the notion that dispositional optimism can influence diurnal cortisol secretion as well as cortisol reactivity. The aim of the present study was to examine whether induced optimism can similarly affect HPA activity and thereby potentially have beneficial health effects. We assigned 66 university students to either the Best Possible Self (BPS) or an active control condition, respectively entailing two weeks of daily visualization of a positive future or time management exercises. Before and after the intervention, we assessed diurnal cortisol levels, response to awakening (CAR), and reactivity to the Trier Social Stress Task (TSST), as well as optimism, affect, negative cognitions, perceived stress, and threat appraisal. Effects of the BPS intervention were tested with repeated measures ANOVA (psychological outcomes) and multilevel regression (cortisol outcomes). The BPS intervention was associated with decreases in both the CAR and cortisol responses to acute stress. Compared to controls, BPS participants showed decreased worrying and increased positive affect post-intervention; however, they did not show the expected greater increase in optimism. Within-person decreases in worrying were associated with decreased CARs, whereas both decreased worrying and increased PA were linked to attenuated stress reactivity. Results suggest that the BPS intervention can influence HPA axis reactivity, with effects on well-being variables likely mediating the process. More research is needed to determine longer-term neuroendocrine and health effects of such interventions in at-risk as well as healthy populations.